2018
DOI: 10.3389/fimmu.2018.00880
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Concepts in Immune Thrombocytopenia

Abstract: Immune thrombocytopenia (ITP) is an autoimmune disease defined by low platelet counts which presents with an increased bleeding risk. Several genetic risk factors (e.g., polymorphisms in immunity-related genes) predispose to ITP. Autoantibodies and cytotoxic CD8+ T cells (Tc) mediate the anti-platelet response leading to thrombocytopenia. Both effector arms enhance platelet clearance through phagocytosis by splenic macrophages or dendritic cells and by induction of apoptosis. Meanwhile, platelet production is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
176
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(201 citation statements)
references
References 234 publications
3
176
2
5
Order By: Relevance
“…After our initial results indicating that unfractionated human BM cells were permissive for DENV infection, we sought to further investigate the contributing cell lineages in human BM susceptible to DENV infection. Previous studies utilizing stem/progenitor cell lines or primate infection models suggested that HSPCs, MkPs, and megakaryocytes were the critical components of DENV infection . Cells infected by DENV‐2 were collected for 2 weeks to mimic the progression of in vivo DENV infection and were subjected to FACS analysis to identify the infected cell phenotypes, while the corresponding supernatants were collected for viral titers by standard plaque assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After our initial results indicating that unfractionated human BM cells were permissive for DENV infection, we sought to further investigate the contributing cell lineages in human BM susceptible to DENV infection. Previous studies utilizing stem/progenitor cell lines or primate infection models suggested that HSPCs, MkPs, and megakaryocytes were the critical components of DENV infection . Cells infected by DENV‐2 were collected for 2 weeks to mimic the progression of in vivo DENV infection and were subjected to FACS analysis to identify the infected cell phenotypes, while the corresponding supernatants were collected for viral titers by standard plaque assay.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, our observations that BM cells from ITP patients in whom thrombocytopenia results from pathologic autoantibodies, impaired megakaryocytopoiesis, and T‐cell–mediated destruction of platelets were less likely to be infected by DENV, implying the pivotal role of megakaryocytes in DENV infection. The autoantibodies are found in approximately 60% of all ITP patients, predominantly against platelet glycoprotein (GP) IIb/IIIa (CD41/ CD61 ) and/or the GP Ib/IX complexes . We speculate that these autoantibodies would inhibit the ability of DENV entry and replication in hematopoietic cells from ITP.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, a direct link regarding autoantibody binding has been demonstrated for several, but not all, autoimmune diseases. Well-established examples for this causal relationship include autoantibodies against thyroglobulin in autoimmune thyroiditis [7][8][9] and glycoproteins IIb and IIIa in immune thrombocytopenia (ITP) 10,11 . Autoimmune skin blistering dermatoses (AIBD) comprise a good illustration of a direct pathogenic contribution of autoantibodies.…”
mentioning
confidence: 99%
“…Low platelet counts increase bleeding risk (26). Thrombocytopenia is a condition in which peripheral blood platelet counts are below 100,000 platelets/ll (17,27,28). Single-dose gamma-ray TBI (6.11 Gy) rapidly reduced mean platelet counts to below 50% of the baseline within 5 days, and below 100 3 10 3 cells/ll within approximately 9 days postirradiation (Fig.…”
Section: Administration Of Plag Mitigates Platelet Loss In Peripheralmentioning
confidence: 99%
“…Patients with neutropenia often experience reduced defense against infection and inflammation, consequently followed by mortality due to sepsis (16). Low platelet counts in peripheral blood confer a greater risk of bleeding and delayed wound healing (17). The contributory mechanisms of radiation-induced immune suppression are complex.…”
Section: Introductionmentioning
confidence: 99%